Antimicrobial activity of aridicins, novel glycopeptide antibiotics with high and prolonged levels in blood. - Grappel, S F (1985)
Three new glycopeptide antibiotics, aridicins A, B, and C, produced by Kibdelosporangium aridum have a spectrum of antimicrobial activity in vitro which is similar to that of vancomycin. The antimicrobial activities of these glycopeptides against clinical bacterial isolates were compared with those of vancomycin and other related glycopeptide antibiotics in vitro by agar dilution and microtiter broth dilution tests and in vivo in mouse protection studies. In vitro they were somewhat less effective than vancomycin against strains of Staphylococcus aureus and less active against coagulase-negative Staphylococcus spp. However, they were more active than vancomycin against strains of Streptococcus faecalis and markedly superior to vancomycin and other glycopeptide antibiotics against strains of Clostridium difficile. In experimental infections, aridicin A was effective against strains of S. aureus, S. epidermidis, Streptococcus faecalis, and Streptococcus pyogenes, although its 50% effective doses were higher than those of vancomycin when administered after infection. After subcutaneous administration, aridicin A had a higher peak level in serum and a longer half-life than vancomycin or teicoplanin. The aridicins were markedly superior to vancomycin when administered prior to infection in mouse protection tests, indicating long-acting potential.